2004
DOI: 10.1080/01650250344000262
|View full text |Cite
|
Sign up to set email alerts
|

Reasoning and negotiation about child responsibility in urban Chinese families: Reports from mothers, fathers and children

Abstract: The study investigates everyday parental practices involved in the transmission of cultural values and extends current literature on parenting in Chinese families. Children aged 6, 8, and 10 years from 240 Beijing families, and both their parents, were asked about ways in which expectations of child responsibility are transmitted through routine requests, reasoning, and negotiation about household work, an area in which Western parents are known to use such practices. Use of a range of parental requests and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…Owing to the basic differences in the characteristics of urban versus rural communities, in China it was found that fathers in urban communities tend to be more involved in childcare than fathers in rural communities (Song, 2004). Thus, fathers in urban communities tend to adopt more egalitarian attitudes toward parental roles; they experience closer interaction with their children, and they show more love and warmth than their counterparts in rural localities (Bowes, Chen, San, & Yuan, 2004). Other reasons for the higher level of involvement among fathers in urban communities have been proposed by Jankowiak (1992), who argued that the percentage of women employed for pay outside of the home is higher in urban communities than in rural communities.…”
Section: The Macrosystemmentioning
confidence: 95%
“…Owing to the basic differences in the characteristics of urban versus rural communities, in China it was found that fathers in urban communities tend to be more involved in childcare than fathers in rural communities (Song, 2004). Thus, fathers in urban communities tend to adopt more egalitarian attitudes toward parental roles; they experience closer interaction with their children, and they show more love and warmth than their counterparts in rural localities (Bowes, Chen, San, & Yuan, 2004). Other reasons for the higher level of involvement among fathers in urban communities have been proposed by Jankowiak (1992), who argued that the percentage of women employed for pay outside of the home is higher in urban communities than in rural communities.…”
Section: The Macrosystemmentioning
confidence: 95%
“…In the opposite situation, in healthy fathers and their sons, this situation did not apply. As suggested by Bowes et al , 12 though their study was conducted in Chinese children and cultural differences should be taken into consideration, gender appears to be an important moderating factor and has complex effects on children's capacity to cope.…”
Section: Introductionmentioning
confidence: 92%
“…It can be inferred that Japanese parents ' tendency to suppress emotions might have adaptive value, making sense within cultural context. Asian parents also use disapproval and shaming to train their children (Bowes, Chen, San, & Yuan, 2004 ;Fung, 1999 ), so that these emotion socialization strategies may not have the negative consequences seen in Western societies (Chin, 2008 ).…”
Section: Experience and R Egulating Of E Motion And P Arent -C Hild Rmentioning
confidence: 99%